An Ecological Momentary Assessment of Self-improvement and Self-evaluation Body Comparisons: Associations with College Women’s Body Dissatisfaction and Exercise - MacIntyre, Rachel I. (Body Image, 2020)
Upward body comparisons are prevalent among college women and associated with body dissatisfaction and disordered eating. However, less is known about distinguishing features of the comparisons themselves as they occur in daily life. The primary purpose of the present study was to examine whether two types of upward body comparisons previously studied experimentally (self-improvement and self-evaluation) are differentially associated with body- and exercise-related outcomes in real-life settings using ecological momentary assessment (EMA). Undergraduate women (N = 74) between 18–25 years (Mage = 20.4, SD = 1.63) completed five surveys on smartphones daily for seven days. EMA measures assessed body comparisons, body dissatisfaction, and exercise cognitions and behaviors. Baseline body dissatisfaction, comparison tendency, and exercise behavior were examined as moderators. Multilevel analyses revealed that both self-improvement and self-evaluation were associated with greater exercise thoughts (ps < .05), but not with changes in body dissatisfaction (ps> .05). Moderator analyses revealed differences between the two types and their associations with outcomes for select subgroups. For example, self-improvement comparisons were associated with fewer exercise thoughts among participants with high baseline exercise behaviors (p < .01). Further research is needed to understand the differences between self-improvement and self-evaluation and the potential protective mechanisms of self-improvement.